Model Development for Reducing Sodium Consumption at the District Level Using a District Health Board Mechanism - Prompunjai, Pairoj; Thammakun, Theerawut; Singthong, Thipphayarat (OSIR Journal; Volume 16 Issue 1 (2023): Outbreak, Surveillance, Investigation & Response (OSIR) Journal, 2023)
High levels of dietary sodium are associated with hypertension and non-communicable diseases. We aimed to develop a model for reducing sodium consumption at the district level using a mechanism developed by the District Health Board (DHB). Hankha District in Chai Nat Province was selected as the study area. The study was conducted between June and December 2022. Research methods included the development of a model to reduce sodium consumption, questionnaires and focus group discussions, and measuring the amount of salt in food and blood pressure levels among study participants. The developed model comprised three measures; monitoring people’s sodium consumption; creating a mechanism for driving and managing the environment contributing to behavioral changes; and providing knowledge and promoting behaviors among groups at high risk for hypertension. After model development, the mean knowledge scores among DHB members and their skills in managing plans and projects were significantly higher than those before the process. Mean knowledge scores, health literacy and proper sodium consumption behaviors among at-risk groups were also higher. In addition, the increased knowledge scores significantly correlated with proper sodium consumption behaviors. Our results should encourage authorities at the policy level to apply a DHB mechanism to reduce sodium consumption in communities. Keywords:  model, sodium consumption, District Health Board